Dominant-negative inhibition of canonical Notch signaling in trophoblast cells does not disrupt placenta formation - Carrie J. Shawber; Dex-Ann Brown-Grant; Tracy Wu; Jan K. Kitajewski; Nataki C. Douglas (Biology Open, 2019)
Proper development and function of the mammalian placenta requires interactions between embryo-derived trophoblasts and uterine endothelial cells to form mosaic vessels that facilitate blood flow to a developing conceptus. Notch signaling utilizes a cell–cell contact dependent mechanism to drive cell behaviors, such as differentiation and invasion. In mice, Notch2 is needed for proper placentation and embryo survival. We used transgenic mice with a dominant-negative form of Mastermind-like1 and Cyp19-Cre and Tpbpa-Cre drivers to inhibit canonical Notch signaling in trophoblasts. Both Cre drivers resulted in robust placental expression of dominant-negative Mastermind-like1. All pregnancies progressed beyond mid-gestation and morphological analyses of placentas revealed no differences between mutants and controls. Our data suggest that mouse placentation occurs normally despite dominant negative inhibition of trophoblast canonical Notch signaling and that Notch2 signaling via the canonical pathway is not necessary for placentation.